PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SEKOLAH DASAR - Tungga, Intan Yunita; Benu, Asti Yunita; Nahak, Roswita Lioba (HINEF : Jurnal Rumpun Ilmu Pendidikan, 2024)
The project based learning model is a learning model that emphasizes or is centered on students, project based learning requires students to be more active, creative in solving problems and can practice and develop communication skills from students, and can provide learning experiences for students in organizing projects to produce products. The purpose of this study was to determine whether there is an influence of the Project Based Learning learning model on the results of learning science in grade V students of UPTD SD Inpres Kuanino 3. This type of research is quantitative research classified as Quasi Experimental research, using a non-equivalent control group design. The sampling technique uses a purposive sampling technique with a sample size of 43 respondents. The instruments used in this study are Observation tests and documentation. Data were analyzed using hypothesis testing or t-tests. The results of this study indicate that the average value of the experimental class posttest and the control class posttest using the t-test is 87.27> 61.90 with a difference of 19.7. Furthermore, through hypothesis testing (Independent Samples Tests) shows that the sig. value. (2-tailed) t-test for Equality of Means of 0.000 < 0.05 means H0 is rejected and Ha is accepted. so it can be concluded that there is a significant influence of the Project Based Learning learning model on the science learning outcomes of class V SD Inpres Kuanino 3 Kupang City.